Pre-treatment of wastes containing keratin in industrial conditions - Mézes, Lili; Bíró, Tibor; Petis, János; Tamás, János (Acta Agraria Debreceniensis, 2008)
The aim of the research was a development of a featherdegradation technology in industrial circumstances. During the experiments we determined the parameters of the critical environmental and technological limitation factors. Because of the high keratin-content the degradation (and composting) of the feather is difficult. With the developed technology huge mass of feather can be used fast and easily in biogas production and in the adjustment of the optimal element ratio of biomass. The industrial experiments were implemented in a 6m3 heatable double-walledtank with stirring-shovels and aeration-system. The degradation process was followed with extinction measurements.According to the experiments that were done the best results were given at the case which was heat-treated at 70°C, was injected with 1% bacteria concentration, and where 1:3 feather:water ratio was set if we consider the effectiveness of degradation and the hydraulical retention time.